The Cochrane Database of Systematic Reviews 2002
DOI: 10.1002/14651858.cd002045
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic versus isotonic crystalloid for fluid resuscitation in critically ill patients

Abstract: Jarvela 2001 {published data only} Jarvela K, Koskinen M, Kaukinen S, Koobi T. Effects of hypertonic saline (7.5%) on extracellular fluid volumes compared with normal saline (0.9%) and 6% hydroxyethly starch after aortocoronary bypass graft surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…There are insufficient data to make a recommendation for or against use of hypertonic saline for shock associated with head injuries or hypovolemia. 333,334 • There is insufficient evidence in infants and children to make a recommendation about the best timing or extent of volume resuscitation for children with hemorrhagic shock following trauma.…”
Section: Special Resuscitation Situations Septic Shockmentioning
confidence: 99%
“…There are insufficient data to make a recommendation for or against use of hypertonic saline for shock associated with head injuries or hypovolemia. 333,334 • There is insufficient evidence in infants and children to make a recommendation about the best timing or extent of volume resuscitation for children with hemorrhagic shock following trauma.…”
Section: Special Resuscitation Situations Septic Shockmentioning
confidence: 99%
“…24 Published evidence of a survival benefit in resuscitation of patients with trauma has been equivocal, and a systematic review of literature published recently did not show any advantage of hypertonic crystalloid solutions over isotonic solutions for fluid resuscitation in patients who are critically ill. 4 However, this product may have an application for patients with severe brain injury because it may expand the circulating blood volume with less risk of the patient having cerebral edema develop.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate volume status of both the ICS and ECS spaces is necessary to obtain this effect; so that, the prolonged usage of HCS crystalloid is not recommended (Maningas and Bellamy 1986;McIlroy and Kharasch 2003). Both Wade et al (1997) and Bunn et al (2002) reported, in their meta-analyses, no significant improvement in outcome in critical patients by using HCS. They hypothesized that the combined used of HCS and colloids would be superior to isotonic fluid resuscitation (Agrò and Vennari 2013b).…”
Section: Hypertonic Crystalloidsmentioning
confidence: 99%